2021
DOI: 10.3389/fcell.2021.674553
|View full text |Cite
|
Sign up to set email alerts
|

Platelets, Constant and Cooperative Companions of Sessile and Disseminating Tumor Cells, Crucially Contribute to the Tumor Microenvironment

Abstract: Although platelets and the coagulation factors are components of the blood system, they become part of and contribute to the tumor microenvironment (TME) not only within a solid tumor mass, but also within a hematogenous micrometastasis on its way through the blood stream to the metastatic niche. The latter basically consists of blood-borne cancer cells which are in close association with platelets. At the site of the primary tumor, the blood components reach the TME via leaky blood vessels, whose permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 207 publications
1
22
0
Order By: Relevance
“…Either way, tumor cells infiltrate the EC layer, thereby causing blood components to leak into the surrounding tissue. Among them are coagulation factors that, similar to wound healing, generate a fibrin-rich ECM [ 412 ]. Even before blood vessel leakage occurs, tumor cells induce the resident cells to change their behavior.…”
Section: Mmps and Tme: More Than A Hit-and-run Relationmentioning
confidence: 99%
“…Either way, tumor cells infiltrate the EC layer, thereby causing blood components to leak into the surrounding tissue. Among them are coagulation factors that, similar to wound healing, generate a fibrin-rich ECM [ 412 ]. Even before blood vessel leakage occurs, tumor cells induce the resident cells to change their behavior.…”
Section: Mmps and Tme: More Than A Hit-and-run Relationmentioning
confidence: 99%
“…GC is one of most common malignancies of the digestive system. There is increasing evidence that platelets can regulate the TME and promote immune escape and, thus, play an important role in tumor progression and metastasis ( Obermann et al, 2021 ). At present, mechanisms related to PFRG regulation of the immune microenvironment are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have indicated that tumorigenesis is closely associated with abnormalities in the coagulation cascade response in the early stage of tumor. The coagulation system is an integral component of the unique vascular microenvironment for tumor proliferation and progress ( 28 , 29 ). FIB and DD, as important factors in the coagulation cascade and fibrinolysis processes, respectively, have been shown to be involved in the invasive process of a variety of malignancies ( 8 , 19 , 30 ).…”
Section: Discussionmentioning
confidence: 99%